Cultural Heritage in International Economic Law - Vadi, Valentina (Brill, 2023)
Can cultural heritage be adequately protected vis-à-vis economic globalization? This book investigates whether and how international economic law governs cultural phenomena by mapping the relevant legal framework, discussing the relevant disputes concerning cultural elements adjudicated before international economic 'courts' (namely the World Trade Organization adjudicative bodies and investment treaty arbitral tribunals), and proposing legal methods to reconcile cultural and economic interests. It thus provides a comprehensive evaluation of possible solutions, including evolution of the law through treaty interpretation and reforms, to improve the balance between economic governance and cultural policy objectives.